2009
DOI: 10.1002/jemt.20723
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural analysis of radicular dentine surface submitted to CO2 laser at different parameters

Abstract: The intensity of the effects is dependent on the laser-irradiation dosimetries. Alterations were more intense when higher parameters were used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Due to the presence of melted areas that might affect the adhesion of fibrin, it appears that CO 2 laser irradiation is not a good choice for surface treatment. 41 In the present study, in the CO 2 group, the smear layer was removed and dentinal tubules were relatively open, but smooth surfaces exhibited decreased fibrin attachment.…”
Section: Discussionmentioning
confidence: 58%
“…Due to the presence of melted areas that might affect the adhesion of fibrin, it appears that CO 2 laser irradiation is not a good choice for surface treatment. 41 In the present study, in the CO 2 group, the smear layer was removed and dentinal tubules were relatively open, but smooth surfaces exhibited decreased fibrin attachment.…”
Section: Discussionmentioning
confidence: 58%
“…The absorption bands of dental structures (enamel, dentin, and cementum) are in the infrared region due to phosphate, carbonate, and hydroxyl groups in the crystalline structure (Fox et al,1992; Klein et al,2005). These absorption bands in the 9.0‐ to 11.0‐μm region coincide closely to the CO 2 laser irradiation (Moshonov et al,2005; Nomelini et al,2009) and hence, the dental hard tissues can efficiently absorb the irradiation from the CO 2 laser (Kwon et al,2005; Moshonov et al,2005). During irradiation, chemical (Chiang et al,2008; Fox et al,1992; Moshonov et al,2005) and morphological (Chiang et al,2008; McCormack et al,1995; Nomelini et al,2009) changes can be induced in the irradiated dental enamel, thereby changing the susceptibility of its modified mineral content to organic acids in the oral environment (Rodrigues et al,2006; Tepper et al,2004).…”
Section: Introductionmentioning
confidence: 84%
“…10,11 These absorption bands are close to the CO 2 laser irradiation. 10,[12][13][14][15][16][17] This is why these tissues can efficiently absorb the irradiation from the CO 2 laser.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with other in vitro studies that have shown that combined laser-fluoride have beneficial effects on enamel microhardness. [5][6][7][8]16,20 This re-hardening effect could be attributed to the physico-chemical changes that have been shown to take place after F-L treatment in several studies as increased micro-porosities in tooth structure, increase in deposition of calcium fluoride on surface, partial conversion of hydroxy apatite to fluoro apatite which becomes trapped in the surface and subsurface enamel and crystal growth related to the temperature change. 1 The two applications of F-L treatment did not show significant difference compared to one-time application.…”
Section: Discussionmentioning
confidence: 99%